Prospective analysis of the effects of RAS mutation on local tumor progression and overall survival after radiofrequency ablation for colorectal liver metastases - Ji-Chen Wang; Yu-Hui Liu; Bin-Bin Jiang; Li-Jin Shao; Song Wang; Wei Yang; Wei Wu; Kun Yan; Zhong-Yi Zhang (International Journal of Hyperthermia)
Objectives To investigate the effects of RAS mutation on local tumor progression (LTP) and overall survival (OS) after radiofrequency ablation (RFA) for colorectal liver metastases (CRLMs).Methods This prospective study consecutively enrolled patients with CRLM who underwent ultrasound-guided RFA between June 2020 and July 2022. RAS mutation status was analyzed via the amplification refractory mutation system PCR method. The safety margin was measured via an anatomic landmark-based manual assessment method. Factors associated with time-to-LTP and OS were assessed via univariate and multivariate analyses.Results A total of 163 patients with 284 ablated tumors were included. Sixty-nine patients (42.3%) had RAS mutations. Compared with the RAS-wild-type group, the RAS-mutant group had a higher 2-year cumulative LTP rate (20.0% vs. 9.8%, p = 0.016) and a worse 2-year OS rate (55.7% vs. 79.8%, p < 0.001). Compared with RAS-wild-type tumors, RAS-mutant tumors had a significantly greater 2-year cumulative LTP rate in the subgroups with safety margins <5 mm (47.6% vs. 24.9%, p = 0.034) and ≥5 mm (8.6% vs. 1.9%, p = 0.045). In the multivariate Fine–Gray analysis, RAS mutation (SHR, 2.42; p = 0.007) and a safety margin <5 mm (SHR, 7.94; p < 0.001) were found to be independent predictors of the time-to-LTP. According to the multivariate Cox analysis, RAS mutation (HR, 2.13; p = 0.010), CEA >5 ng/mL (HR, 2.29; p = 0.017), and extrahepatic metastases (HR, 2.04; p = 0.016) were independent predictors of shorter OS.Conclusions RAS mutation was an independent predictor of LTP and OS after RFA for patients with CRLM. RAS-mutant tumors require wider safety margins.